DEVELOPMENT OF A REAGENT KIT FOR THE DETECTION AND TYPING OF THE “WEST” TOPOTYPE OF BLUETONGUE VIRUS SEROTYPE 9 (BTV-9W) IN BIOLOGICAL SAMPLES USING RT-qPCR - Ivanova, K.R.; Nizkorodova, A.S.; Zhigailov, A.V.; Berdygulova, Zh.A.; Kulemin, M.V.; Ostapchuk, Ye.O.; Naizabayeva, D.A.; Mamadaliyev, S.M.; Skiba, Y.A. (Eurasian Journal of Applied Biotechnology, 2025)
Bluetongue (BT), also known as sheep catarrhal fever, is a highly pathogenic viral infection caused by the bluetongue virus (BTV). This disease holds significant economic importance as it is characterized by high mortality rates, reduced productivity, deteriorated animal health, and economic losses. Kazakhstan is considered free from BT, but the primary vectors of BTV, midges of the genus Culicoides, are widely distributed throughout the country. Southern Kazakhstan offers favorable conditions for the reproduction of midges, and the high density of susceptible livestock combined with the import of animals from BTV-endemic regions creates a significant risk of virus spread. This underscores the need for the development of a domestic test system for the detection of BTV via quantitative PCR, capable of differentiating vaccine strains from field strains of the virus. This study presents the results of development and validation of a PCR test system for the diagnosis of BT. During development, real-time reverse transcription PCR (RT-qPCR) was utilized for the precise detection of BTV, enabling identification of small amounts of viral RNA in biological samples. The kit is based on primers and a fluorescently labeled probe targeting a conserved region of BVT genome (segment 10), ensuring high specificity and ability to detect various virus serotypes. This test system will be in demand in market and will enhance food security in country.